The effects of COVID-19 on pharmacotherapy in patients with chronic diseases (Research, Society and Development, 2021)
The COVID-19 pandemic, caused by a new strain of coronavirus, has created great challenges throughout the world. This disease has the power to develop complications, higher morbidity and mortality when compared to other diseases, and a higher prevalence of hospitalizations in patients with Systemic Arterial Hypertension (SAH) and Diabetes Mellitus (DM). This study aimed to evaluate the effects of COVID-19 on pharmacotherapy in patients with chronic diseases. This is a descriptive, exploratory research with a qualitative and quantitative approach, carried out at FAINOR's Health Clinic. The sample for this study consisted of 20 patients, with the inclusion criteria being patients with chronic diseases, exclusively SAH or DM who had COVID-19 disease. As exclusion criteria, patients who did not have the disease. The data were collected through a questionnaire applied in an electronic format. Of the patients diagnosed, about 50% had isolated DM, 20% had isolated hypertension, 30% had associated DM and hypertension, and 30% were obese/overweight. About 70% of these people developed sequelae from the coronavirus, such as dehydration, body aches, dry cough, forgetfulness, and Acute Renal Failure. Approximately 40% of these patients had serious drug interactions in their treatments for SAH and DM, as well as concomitant SARS-CoV-2 treatment. It was concluded from the data collected in the survey that for SAH and DM the questionnaire elicited responses that indicated that the pandemic COVID-19 did not generate noticeable changes in the pharmacotherapy of the participants. However, the virus reflected negatively on the general health condition of the patients, causing sequelae in many of them.